POLITICAL RIGHTS PROTECTION IN REGIONAL ELECTION: EVALUATION PERSPECTIVE OF REGIONAL EXPANSION IN INDONESIA - Oly Viana Agustine; Anna Triningsih (Faculty of Law, Universitas Jenderal Soedirman, 2021)
The reforms that took place in Indonesia brought the spirit of decentralization which was reflected in various formation, expansion, abolition and merger of regions. The high development of regional expansion is aimed at providing community welfare. In line with the formation of several newly created regions, various problems have emerged, especially in relation to the implementation of protecting the political rights of citizens in regions experiencing regional expansion. This research will discuss about how to protect the political rights of citizens in the evaluation of regional expansion in Indonesia. The results showed that in the expansion of regions, proportional considerations are needed in relation to public participation. The neglect of democratic principles in the implementation of public participation causes the violation of the political rights of citizens in regional expansion. Therefore, in regional expansion, public participation is needed as a form of democracy in protecting citizens' political rights.Keywords: Evaluation; Indonesia; Protection of Political Rights, Regional Expansion